Unveiling the Effectiveness of Agency Cost and Firms’ Size as Moderators Between CSR Disclosure and Firms’ Growth - Akram, Aswad; Tang, Yingkai; Tariq, Jasim (Frontiers in Psychology, 2020)
Doubtlessly, the excelled corporate governance orientates towards adopting CSR activity which boosts the firms’ growth. In this regard, this study has evaluated that CSR disclosure enhances the firms ‘growth. Specifically, agency cost and firm ‘size have been analyzed as moderators which influence the firms’ performance asymmetrically. The data of 300 manufacturing Pakistanis listed companies on SECP have been accumulated for the years 2010-2018. Empirical results have concluded that agency cost as a moderator is detrimental for firms’ growth while firms’ size as a moderator is blessing in disguise for the firms’ growth. Moreover, firms having leverage decelerates the firm’s growth while the presence of independent directors augments the firms’ growth. Significantly, our results are reliable through implementation of 2SLS instrumental panel regression.